The Pengaruh Pengembangan Industri Terhadap PDB Tiongkok - Stella Yosephine (Politeknik Kutaraja, 2021)
This study explains China's economic development through the calculation of sectoral shares to GDP. This study applies correlational principles with quantitative data and the variables used in this study are industry, services and agriculture. Starting from the agricultural sector, then becoming very weak due to the industrialization program but in 2010, more than 70% of China's FDI was channeled into the service sector and since 1999 China has been active as a lender for other countries which makes it easier to do trade in various countries. The influence of China's industrial sector has never been separated from the sector that dominates GDP, although this sector still does not dominate due to the real dominance of the trade sector, which is included in the service sector. Author recommends that China should offer loans with more terms and offer many benefits for people moving from the agricultural sector to the industrial sector.